Falls in older patients with cancer: Nursing and Allied Health Group of International Society of Geriatric Oncology review paper. Issue 1 (January 2020) - Sattar, Schroder; Kenis, Cindy; Haase, Kristen; Burhenn, Peggy; Stolz-Baskett, Petra; Milisen, Koen; Ayala, Ana Patricia; Puts, Martine T.E.
ABSTRACT: Background: Falls are a major health issue in older adults and are of greater concern among those with cancer due to effects of cancer and its treatments. This paper provides an overview of current literature on fall screening/assessment and interventions and a succinct summary of recommendations for oncology nurses to support this vulnerable population. Methods: A comprehensive search for literature reviews on falls was conducted in Medline and CINAHL. A comprehensive Internet search was also performed for known guidelines on fall prevention and/or management published within the past 10 years. Search results were compared, contrasted, and summarized to develop clinical recommendations for nurses working with older adults with cancer. Levels of evidence were reported based on the Oxford Centre for Evidence-based Medicine. Results: Six guidelines and 17 systematic reviews were identified. Having a history of falls was the most commonly identified fall risk factor/predictor. Multifactorial intervention and exercise appear to be the most commonly recommended. No fall assessment tools were consistently recommended as a reliable means of identifying those at risk for falls. Conclusion: Assessing older patients for falls and fall risks is an important first step to identify those who may require further follow-up and intervention. Oncology nurses play a key role in optimizing health outcomes of older adults with cancer - through the use of evidence-based information, such as presented in this publication - and have the capacity to help reduce fall risks during and after treatment through information provision, advocacy, support, and promotion of physical activity.